β-mannanase supplementation in diets reduced in 85 kcal metabolizable energy/kg containing xylanase-phytase improves gain to feed ratio, nutrient usage, and backfat thickness in finisher pigs - Jansller Luiz Genova; Paulo Evaristo Rupolo; Liliana Bury de Azevedo; Daniela Henz; Silvana Teixeira Carvalho; Marcos Kipper; Giovana de Arruda Castelo Gonçalves; Hellen Lazarino Oliveira Vilela; Tiago Junior Pasquetti; Newton Tavares Escocard de Oliveira; Andrei Roberto Manelli Dietrich; Paulo Levi de Oliveira Carvalho (Frontiers in Veterinary Science, 2023)
This study aimed to assess the effects of β-mannanase supplementation in metabolizable energy (ME)-reduced diets containing xylanase-phytase on performance, fecal score, blood biochemical and immunological profile, apparent total tract digestibility (ATTD), digesta passage rate, fecal microbiome, carcass traits and meat quality in finisher pigs (n = 40 entire male hybrid, 26.0 ± 0.9 kg) randomly assigned to 1 of 4 dietary treatments: a control diet containing isolated phytase and xylanase valued at 40 kcal of ME/kg (CD0), CD0 + β-mannanase (0.3 g/kg valued at 30 kcal of ME/kg) (CD70), CD0 + β-mannanase (0.3 g/kg valued at 45 kcal of ME/kg) (CD85), and CD0 + β-mannanase (0.3 g/kg valued at 60 kcal of ME/kg) (CD100), with 10 pen replicates. Pigs fed CD0 diet showed (P = 0.002) greater ADFI. However, pigs fed CD0 diet showed (P = 0.009) lower G:F than those provided CD70 or CD85 diets. A greater (P < 0.001) superoxide dismutase concentration was observed in pigs fed CD70 diet. Pigs fed CD85 diet showed (P = 0.002) greater digestible protein than pigs fed CD0 or CD100 diets. Pigs fed CD70 diet showed an increase of 11.3% in digestible protein than those fed CD0 diet. In addition, greater (P < 0.001) digestible energy was observed in pigs fed CD85 diet. Pigs fed CD0 or CD100 diets showed greater (P < 0.05) Firmicutes:Bacteroidota ratio than those fed CD85 diet. The Muribaculaceae was more abundant (P = 0.030) in pigs fed CD70 diet than in those fed CD0 diet. The Prevotella was more abundant (P = 0.045) in pigs fed CD85 diet than in those fed CD100 diet. In conclusion, β-mannanase supplementation in diets containing xylanase-phytase allows reducing 85 kcal of ME/kg because it improves gain to feed ratio, energy and protein usage, and backfat thickness without metabolic and intestinal ecosystem disorders in finisher pigs.